A sonification algorithm for developing the off-roads models for driving simulators. (1st January 2018) - Chiroiu, Veturia; Brişan, Cornel; Dumitriu, Dan; Munteanu, Ligia
Highlights: High fidelity model of 3D normal vibro-contact problem with friction. Dynamic road concept to characterize a particular stretch of road. Multiple data base of the sonification capability-off road and on road. Easily integrated with many visual display systems in the driving simulator platforms. Abstract: In this paper, a sonification algorithm for developing the off-road models for driving simulators, is proposed. The aim of this algorithm is to overcome difficulties of heuristics identification which are best suited to a particular off-road profile built by measurements. The sonification algorithm is based on the stochastic polynomial chaos analysis suitable in solving equations with random input data. The fluctuations are generated by incomplete measurements leading to inhomogeneities of the cross-sectional curves of off-roads before and after deformation, the unstable contact between the tire and the road and the unreal distribution of contact and friction forces in the unknown contact domains. The approach is exercised on two particular problems and results compare favorably to existing analytical and numerical solutions. The sonification technique represents a useful multiscale analysis able to build a low-cost virtual reality environment with increased degrees of realism for driving simulators and higher user flexibility.